Valvular Heart Disease and Pregnancy in the Delivery Room at Yalgado Ouedraogo University Hospital about 12 Cases - Koudougou Jonas Kologo; Georges Rosario Christian Millogo; Mbaye Salissou Seck Mbaye; Relwendé Aristide Yaméogo; Hermann Adoko; Germain Mandi; W Bernard Ouedraogo; Adolphe Zingué; Anna Thiam/Tall; André K. Samadoulougou (Journal of Hypertension and Cardiology, 2022)
This series summarizes 12 pregnancies complicated by valvular heart disease, focusing on intrapartum management, anesthesia choices, and maternal–fetal outcomes in a resource‑limited setting.
Keywords: Heart